Analisis Faktor yang Mempengaruhi Corporate Social Responsibility Disclosure pada Perusahaan Pertambangan - Irena, Irena (Jurnal Ekonomi, 2019)
This research aims to examine and analyze the influence of profitability, leverage, company size and size of board of commissioner partially on CSRD in mining companies listed on the Indonesia Stock Exchange (IDX) period 2012-2016. The method used in this research is quantitative descriptive research. Population in this research is all mining companies listed in IDX period 2012-2016, which is 36 companies. Based on the sample selection method, the number of companies selected to be the research sample is 25 companies. The technique of data analysis used is multiple linear regression analysis. The result of this research is company size and size of board of commissioner had significant influencepartiallyto CSRD on mining companies listed on IDX period 2012-2016.